EFEKTIFITAS STRENGTENING BICYCLE CRUNCH EKSTREMITAS BAWAH TERHADAP MENSTRUASI MAHASISWA AKBID GMC - Intarti, Wiwit Desi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Menstruation is the spending of vaginal fluid from periodically during the reproductive age. Normal menstrual cycle is 28 days long with mentruasi 3-5 days. Many factors affect the mentruasi (the menstrual cycle, the old and the problems that arise when the menstruation). Considering a long menstrual bleeding can cause menstrual cycles become irregular so give impact on fertility levels and even infertility occurs, then there are techniques for strengthening muscles of the abdomen. Strengthening bicycle crunch which serves to make the elastic abdominal muscles, which may affect the flexibility of the muscles of the uterus. So the menstrual cycle becomes normal. The purpose of the research is to find out the effectiveness of strengthening bicycle crunch of lower extremities towards menstruation Akbid GMC students. This type of research was experimental research. The population of the research a number of 33 subjects of research. We used total sampling for chose the technique sample. Measuring instrument research was the dress, which was to assess the amount of menstrual blood, menstrual and observation sheet check list to control the regularity of the exercise.The results showed that mentruasi old changes into normal, with value t calculate > t table (2,273 > 2.042. In addition, the amount of blood that comes out more and more with a value of 0.001 p. The conclusion from this study is there is effectiveness strengthening bicycle crunch of lower extremities towards menstruation Akbid GMC students. Keywords: strengthening bicycle crunch, menstruation, student